Electromagnetic Compatibility Analysis of DVB-T and LTE Systems - Aleksandravicius, Jurgis; Krivochiza, Jevgenij; Aleksiejunas, Rimvydas; Svirskas, Kestutis; Zilinskas, Mindaugas (Elektronika ir Elektrotechnika, 2016)
In 2012 the Communications Regulatory Authority of Lithuania reallocated 790–862 MHz band used by terrestrial TV operators for mobile communications purposes following an International Telecommunication Union decision. The aim of this paper is to experimentally investigate electromagnetic compatibility of Digital Video Broadcasting - Terrestrial receivers operating below 790 MHz band with LTE base stations operating in 800 MHz band and derive an analytical model suitable for further electromagnetic compatibility analysis. An experimental testbed using LTE hardware and DVB-T receivers was used for evaluation of adjacent channel LTE downlink signal interference impact on digital TV system. Also, effect of using third party hardware such as band-pass filters and wideband preamplifiers on interference was analyzed. The results obtained provide protection ratio and overloading threshold for the digital TV receivers in different operating scenarios which serve as a reference guide for regulatory authority, mobile operators and terrestrial TV providers. DOI: http://dx.doi.org/10.5755/j01.eie.22.4.15923